Pengaruh Kecerdasan Majemuk Terhadap Karakter Mahasiswa Fakultas Ilmu Pendidikan Universitas Negeri Medan - Anis Andina; Arina Rafa Dina; Astiyah Andini; Inestasia Br. Simanjuntak; Rahel Sentina Stefani Aritoang; Yolanda Agustina Sihombing (Jurnal Pena Pendidikan Dasar, 2025)
This study aims to analyze the relationship between multiple intelligences and character development among students of the Faculty of Education, Universitas Negeri Medan, in the context of twenty-first-century education. The study employed an observational approach with descriptive statistical analysis to obtain an empirical overview of students’ multiple intelligences profiles and character traits as prospective educators. The participants consisted of 25 students from four study programs, namely Primary School Teacher Education, Guidance and Counseling, Early Childhood Teacher Education, and Community Education. Data were collected through direct observation using a checklist-based instrument covering indicators of multiple intelligences and student character. Multiple intelligence data were analyzed using mean scores and distribution across low, moderate, and high categories, while character data were analyzed through frequency and percentage distributions. The results indicate that most students demonstrate moderate to high levels of multiple intelligences, with naturalistic, musical, and verbal-linguistic intelligences emerging as the most dominant. In terms of character development, resilience and discipline were found to be at a high level, whereas independence and initiative remained relatively low. These findings suggest that students’ multiple intelligence potential has not yet been optimally translated into consistent character-related behaviors. Therefore, it is necessary to strengthen learning strategies that systematically integrate multiple intelligences development with character education through contextual, participatory, and reflective approaches in order to foster independent, responsible, and professional future educators.